PENGGUNAAN MEDIA VISUAL UNTUK MENINGKATKAN PEMAHAMAN KONSEP IRISAN BIDANG DENGAN BANGUN RUANG PADA SISWA - ., Asdar (Makassar Journal of Social Sciences, 2015)
Abstract: Mathematics is one of the difficult subjects perceived by many students. This is because the abstract mathematical objects, so students are difficult to understand. Thus, learning mathematics needs to be put in accordance with students' cognitive abilities, mengkongkritkan abstract mathematical objects so that young students understood. From the experience of researchers in teaching over the years, many students have difficulty understanding the three-dimensional material in particular slices of a field with geometry. It is necessary to research that aims to improve students' understanding of the concept of a field with a wedge geometry, the research object class X-5 SMAN 1 Majene academic year 2010/2011. The approach taken in this study is a qualitative approach using classroom action research design. Implementation of the actions carried out in two cycles, the first cycle is the implementation of learning material with slices of a field sketch geometry with media images, and the second cycle of implementation of instructional material slices of a field with geometry with visual media or media-based power point presentation. The data were obtained by observation, administration of questionnaires, and test the research object. Data obtained from observation and questionnaires were analyzed by means of qualitative analysis, while data obtained from the test were analyzed by quantitative anlisis. The results showed that students' mastery of the material slices of a field with geometry> 80% with an average of 88.6 and the final test results 68% of students say that the use of visual media can increase understanding in learning slices field with geometry.